2019
DOI: 10.3390/insects10080223
|View full text |Cite
|
Sign up to set email alerts
|

Using Gamma Irradiated Galleria mellonella L. and Plodia interpunctella (Hübner) Larvae to Optimize Mass Rearing of Parasitoid Habrobracon hebetor (Say) (Hymenoptera: Braconidae)

Abstract: We evaluated possible improvements to the mass rearing of the larval parasitoid Habrobracon hebetor (Say) (Hymenoptera: Braconidae) on irradiated host wax moth Galleria mellonella L. and Indian meal moth Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae) larvae. The use of irradiated G. mellonella and P. interpunctella larvae at the dose of 150 Gy proved useful for enhancing the parasitism and adult emergence of H. hebetor due to the absence of negative repercussions on parasitoid development. Overall, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…evanescens , in terms of more gradual egg “maturation”. In an earlier comparison of these two species as hosts of the larval ectoparasitoid Harbobracon hebetor (Say) (Hymenoptera: Braconidae), Hasan et al [ 29 ] considered G . mellonella as a superior host, due to certain larval characteristics, such as size and longevity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…evanescens , in terms of more gradual egg “maturation”. In an earlier comparison of these two species as hosts of the larval ectoparasitoid Harbobracon hebetor (Say) (Hymenoptera: Braconidae), Hasan et al [ 29 ] considered G . mellonella as a superior host, due to certain larval characteristics, such as size and longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the difference between the two egg age groups for G. mellonella can be narrower as compared with the respective figures of P. interpunctella, which indicates that G. mellonella can be more suitable as a host for T. evanescens, in terms of more gradual egg "maturation". In an earlier comparison of these two species as hosts of the larval ectoparasitoid Harbobracon hebetor (Say) (Hymenoptera: Braconidae), Hasan et al [29] considered G. mellonella as a superior host, due to certain larval characteristics, such as size and longevity. Paradoxically, our data illustrate that 2 d-old eggs of this host species maintain a good level of suitability for parasitism by T. evanescens, for a long period of time, which means that 2 d-old eggs are less affected by storage periods as compared with those of P. interpunctella.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, generalizations regarding the "optimum" conditions that are related with diapause should be avoided, as any "diapause"-related control strategy may not be accurate. On the other hand, considering that P. interpunctella is an ideal species to rear insect parasitoids, standardization of life table characteristics of a given population may be valuable to produce large numbers of parasitoids whenever these are needed 70,71 . Hence, considering our results, we have found that larvae of P. interpunctella can be used with success at various conditions, as the effect of different photoperiod regimes does not drastically affect diapause induction, when these larvae are reared at 17 °C.…”
Section: Discussionmentioning
confidence: 99%
“…For making the mass rearing of parasitoids more efficient, the host insect larvae are being irradiated (Cancino, Ruiz, Viscarret, Sivisnki, & Hendrichs, 2012; Hendrichs et al., 2009). Parasitoids reared on irradiated host demonstrated better fitness due to the reduced immunological response of hosts (Hassan, Yeasmin, Athanassiou, Bari, & Islam, 2019; Muhammad, Ahmad, Rashidi, & Ahmad, 2013; Sarwar, Ahmad, Rashid, & Masoom‐Shah, 2015). Some other studies showed that the irradiation of host insects undermines their defence, prevents their development and triggers a faster development of the parasitoids (Cai et al., 2018; Cancino, Ruiz, López, & Sivinski, 2009; Carton, Poiríe, & Nappi, 2008; Costa, Pachea, Lopez, Botteo, & Mastrangelo, 2016; Dubovskii et al., 2010; Hepdurgun, Turanli, & Zümreoğlu, 2009; Silva, Boleli, & Simoes, 2002; Suárez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%